Within-session reliability and criterion validity of ADR Jumping photocell in the estimation of CMJ - Villalon-Gasch, L.; Jimenez-Olmedo, J. M.; Penichet-Tomas, A.; Olaya-Cuartero, J. (Journal of Physical Education and Sport, 2023)
Vertical jump height is a key measure of lower limb power and performance in many sports and athletic activities. Accurate measurement of vertical jump height is essential to monitor progress, set goals, and design training programs. Besides, new more economical and manageable instruments are emerging. However, it is necessary to know if these devices can measure with the required precision and accuracy. This study examines the concordance (criterion validity) between a new portable photocell ADR jumping and the jump mat Chronojump. Additionally, the within-session test-retest reliability (internal consistency) of CMJ was studied. Twelve highly trained female volleyball players (age: 21.7 ± 2.9 years; height: 1.73 ± 0.06 m; body mass 64.3 ± 7.6 kg; body mass index (BMI): 16.6 ± 2.5 kg/cm2: training experience 8.5 ± 1.8 y). Following a standardized warm-up and a resting period of 5 minutes, 10 CMJs were executed, resting for 2 minutes for each attempt. All records were collected simultaneously by the ADR jumping photocell and the Chronojump Jump mat to compare data from both devices. The within-session test-retest reliability was evaluated using the first three jumps of all participants. The agreement between devices was near-perfect (r = 0.95; CCC = 0.94; SEM = 1.47 cm; Regression Slope=0.99), However, significant differences were detected between instruments (0.81 cm p < 0.05, ES = 0.2). Within-session reliability was slightly higher in ADR jumping (ICC = 0.93; CCC = 0.90; SEM = 1.3 cm; CV = 4.89%) than Chronojump (ICC = 0.91; CCC = 0.87; SEM = 1.6 cm; CV = 6.0%). Furthermore, sensitivity was higher for ADR jumping (SWC = 0.37 cm) than for the Chronojump (SWC = 0.45 cm). The noise of the measurement (SEM) was greater than the worthwhile change (SWC), indicating a lack of capacity to detect meaningful changes. In conclusion, the ADR jumping photocell is a valid instrument when compared to the Chronojump jump mat in the measurement of CMJ. In addition, ADR jumping shows high internal consistency values, therefore, can be considered a reliable device for the within-session test-retest in the measurement of CMJ in highly trained female athletes.